ANALISIS STATISTIK PENGUJIAN TEGANGAN TEMBUS IMPULS RSMEO (RUBEER SEED METHYL ESTER OIL) - Andrey Ericson Simarmata, (2023)
The transformer is equipped with insulating oil which is used as insulation in the transformer. Insulating oil must have the ability to withstand breakdown voltage properly to maintain continuity in flowing electricity. However, insulating oil that is circulated and used in transformers generally comes from natural resources in the form of petroleum with several drawbacks such as being less environmentally friendly, impracticable and difficult to decompose. in this study the aims were to make methyl ester oil based on rubber seed, test and compare the value of the impulse breakdown voltage with mineral oil which is commonly used as an insulating medium for trensformers. The processes carried out in this study were stripping, drying and pressing to obtain rubber seed oil, then trans esterification process was carried out to convert the oil into methyl ester, and impulse penetration testing and analysis of the test results. The results of this study show that the impulse breakdown voltage at RSMEO is at 97.73 kV, while mineral oil is at 140.67kV